2003
DOI: 10.1046/j.1365-8711.2003.06396.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray scaling properties of early-type galaxies

Abstract: We present an analysis of 39 X‐ray luminous early‐type galaxies observed with the ROSAT PSPC. Using multicomponent spectral and spatial fits to these data, we have measured halo abundance, temperature, luminosity and surface brightness profile. We compare these measurements to similar results from galaxy groups and clusters, fitting a number of relations commonly used in the study of these larger objects. In particular, we find that the σ–TX relation for our sample is similar to that reported for clusters, con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 74 publications
14
139
1
1
Order By: Relevance
“…With ROSAT PSPC observations, O'Sullivan et al (2003) found that the relation between the central stellar velocity dispersion and the temperature obtained from X-ray emission is similar to that for clusters and the relation between the X-ray luminosity and the temperature has a steep slope comparable to that found for galaxy groups.…”
Section: Introductionmentioning
confidence: 55%
“…With ROSAT PSPC observations, O'Sullivan et al (2003) found that the relation between the central stellar velocity dispersion and the temperature obtained from X-ray emission is similar to that for clusters and the relation between the X-ray luminosity and the temperature has a steep slope comparable to that found for galaxy groups.…”
Section: Introductionmentioning
confidence: 55%
“…The observed L X -kT relation of FJ sources is shown in Figure 6 with previous works obtained from early-type galaxies, groups of galaxies, and clusters of galaxies (White et al 1997;Xue & Wu 2000;O'Sullivan et al 2003) for comparison, and the possible origins and corresponding objects for FJ sources discussed above are summarized in Table 5. Note that luminosities for FJ sources without redshift information were not calculated and therefore Figure 6 does not include them.…”
Section: Corresponding Object and Origin Of Fj Sourcesmentioning
confidence: 74%
“…The value of r c in most other galaxies with hot gas is less than 1 kpc, which is significantly smaller than the radius of closest approach for all objects in the sample. Therefore, the value of r c is not relevant for our sample, and we can write the density function as a power law, n / r À3 , and we choose to examine n / r À3/2 , as this is similar to that found for the hot gas in ellipticals ( ¼ 1/2 in the ''beta'' models used for ellipticals; e.g., O'Sullivan et al 2003). While this leads to a gas mass that increases with radius as r 3/2 and an emission measure that increases logarithmically with radius, the column density is convergent at large radius.…”
Section: Galactic Halo Modelsmentioning
confidence: 99%